A stochastic viscoelastic–viscoplastic constitutive model and its application to crumb rubber modified asphalt mixtures. (5th January 2016) - Bai, Fan; Yang, Xinhua; Zeng, Guowei
Abstract: An idealized asphalt mixture is modified with either fine or coarse rubber particles by a dry process. A large number of uniaxial compression tests are performed upon samples of the idealized asphalt mixture and the fine and coarse crumb rubber modified (CRM) asphalt mixtures. A stochastic viscoelastic–viscoplastic constitutive model with a lognormally distributed random parameter is proposed to describe their mechanical behaviors. It is shown that the model can approximately predict the probability distribution of the random material strain responses. The influences of the crumb rubber modifiers on the material mechanical properties are quantitatively evaluated. It is found that the fine CRM asphalt mixture exhibits the largest elasticity among the three asphalt mixtures considered. Graphical abstract: Highlights: The random creep and recovery behavior of rubberized asphalt mixture is studied. The stochastic viscoelastic–viscoplastic model can predict random material behavior. The addition of fine rubber particles effectively improves the elasticity of mixture.